MgCl2 center dot 6C(6)H(11)OH: a high mileage porous support for ziegler-natta catalyst - Gnanakumar, Edwin S.; Thushara, K. S.; Gowda, Ravikumar R.; Raman, Sumesh K.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2012)
A new and single phase molecular adduct of MgCl2 with six cyclohexanol molecules MgCl2 center dot 6C(6)H(11)OH (MgCyOH) has been synthesized. Structural insight to this adduct was obtained by a variety of physicochemical methods. C-13 CPMAS spectrum and single pulse MAS spectra with high power proton decoupling recorded at different relaxation time showed the presence of two different sets of magnetically unequal cylcohexanol molecules present around Mg2+. A Raman feature of MgCyOH at 712 cm(-1) confirms that cylcohexanol molecules are present around Mg2+ in an octahedral environment. MgCyOH has been used as support material to prepare Ziegler-Natta (Z-N) active catalyst. Textural property of above Z-N catalyst exhibits high surface area (236 m(2)/g) with high porosity. Above active catalyst has been screened for ethylene polymerization. Depending on the cocatalyst employed (Me3Al, Et3Al, and iso-Bu3Al) and ethylene pressure, polyethylene yield varies an order of magnitude, from 378 to 3570 g/g catalyst, indicating a possible creation of different active sites and different interaction between cocatalyst and catalyst.

MgCl2 center dot 6CH(3)OH: a simple molecular adduct and its influence as a porous support for olefin polymerization - Gnanakumar, Edwin S.; Gowda, Ravikumar R.; Kunjir, Shrikant; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (ACS Catalysis, 2013)
A single phase molecular adduct, MgCl2 center dot 6CH(3)OH has been synthesized using MgCl2 and the simplest alcohol, methanol. Structural, spectroscopic, and morphological studies have been carried out for a better understanding of the single phase MgCl2 center dot 6CH(3)OH adduct. C-13 CPMAS solid state NMR studies show all six methanol molecules are magnetically equivalent and present in a single environment around the Mg2+ center. Raman spectral analysis of the characteristic peak at 708 cm(-1) substantiates octahedral coordination of six CH3OH molecules around Mg2+. Solid state C-13 NMR measurements, made after heat treatment at different temperatures, have been utilized to understand the variations in CH3OH stoichiometry and coordination around Mg2+ with temperature. A titanated active catalyst, TiCl4 on MgCl2 center dot 6CH(3)OH, has also been synthesized and subjected to detailed characterizations. The active catalyst shows high surface area (102 m(2)/g) and mesoporosity. The titanated catalyst has been screened for ethylene polymerization reactions using different cocatalysts (R3Al; R= -CH3, -CH2CH3, and -CH2CH(CH3)(2)). A total of 7.25 kg of polyethylene per gram of catalyst has been obtained with Me3Al cocatalyst, which is six times higher in activity compared with commercial Me3Al/TiCl4/MgCl2 center dot 6EtOH-supported orted catalystAlthough porosity influences the catalytic activity, other factors also seem to contribute to the total catalytic activity.
Keywords: heterogeneous catalysis; MgCl2; Molecular adduct; olefin polymerization; Ziegler-Natta catalyst

9-Fluorenemethanol: an internal electron donor to fine tune olefin polymerization activity - Gnanakumar, Edwin S.; Chokkapu, Eswara Rao; Kunjir, Shrikant; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (Dalton Transactions, 2014)
A new MgCl2 based molecular adduct has been synthesized with 9-fluorenemethanol (9FM) as a novel internal electron donor (IED), along with ethanol (EtOH) (MgCl2 center dot n9FM center dot xEtOH). The above molecular adduct has been subjected to a variety of structural, spectroscopic and morphological characterization techniques. The results of the solid state C-13 CPMAS NMR technique suggests the coordination of 9FM to MgCl2. Observation of a low angle diffraction peak at 2 theta = 5.7 degrees (d = 15.5 angstrom) underscores the coordination of 9FM along the z-axis, and ethanol in the molecular adduct. Active Ziegler-Natta catalysts were prepared by two different synthesis methods; the conventional method to obtain a high surface area active catalyst, and other one with 9FM as an integral part of the active catalyst in order to study the influence of 9FM as an IED over the active sites. The active catalysts were also characterized thoroughly with different analytical tools. The XRD results show (003) facets of delta-MgCl2 (alpha-MgCl2) for the conventional (non-conventional) titanated catalyst. Results of the ethylene polymerization activity study reveals that the conventionally prepared highly porous active catalyst shows 1.7-2.5 times higher activity than the non-conventional prepared catalyst; however, the latter shows a low molecular weight distribution and confirms the role of the Lewis base as an IED.